Characterization of soft-combustion-derived NASICON-type Li2Co2(MoO4)3 for lithium batteries - PRABAHARAN, S (2004)
This work describes the synthesis of a new polyanion material, Li(2)CO(2)(MoO(4))(3), belonging to the NASICON family. A low-temperature soft-combustion method using glycine as a soft-combustion fuel was adopted to obtain single-phase powders of the new material at a temperature as low as 300degreesC. Li(2)Co(2)(MoO(4))(3,) was found to crystallize in an orthorhombic structure (space group Pmmm) with lattice parameters a = 17.584(7) A, b = 10.464(4) A and c = 5.102(9) A. The electronic state of each element present in the new material was confirmed by X-ray photoelectron spectroscopic analysis. The powders were analyzed using inductively coupled plasma emission spectroscopy. The microstructural analysis revealed that the particles (5-10 mum) have a rather columnar shape. The electrochemistry redox behavior of. the new material was studied, for the first time, and the material as positive electrode was found to exhibit topotactic Li(+) extraction/insertion in lithium-containing test cells. (C) 2004 Elsevier B.V. All rights reserved.